Exploring the Tensions and Ambiguities of University Department Chairs - Armstrong, Denise E; Woloshyn, Vera E (Canadian Journal of Higher Education, 2017)
The department chair is a complex middle-management position located at the organizational fulcrum between faculty and senior administration. This qualitative study sought to develop a deeper understanding of chairs’ experiences when enacting their dual roles as managers and scholars. Using a basic interpretative study design, we interviewed 10 department chairs from a medium-sized Canadian university. The participants identified three interrelated areas of challenge: managing position, managing people, and managing self. We discuss the tensions and ambiguities inherent within these themes, along with specific recommendations for supporting this position.